2017
DOI: 10.1371/journal.pcbi.1005385
|View full text |Cite
|
Sign up to set email alerts
|

Classification and adaptive behavior prediction of children with autism spectrum disorder based upon multivariate data analysis of markers of oxidative stress and DNA methylation

Abstract: The number of diagnosed cases of Autism Spectrum Disorders (ASD) has increased dramatically over the last four decades; however, there is still considerable debate regarding the underlying pathophysiology of ASD. This lack of biological knowledge restricts diagnoses to be made based on behavioral observations and psychometric tools. However, physiological measurements should support these behavioral diagnoses in the future in order to enable earlier and more accurate diagnoses. Stepping towards this goal of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 54 publications
6
114
1
1
Order By: Relevance
“…The FDA‐sub model had the best validation performance with a false positive rate of 19/154 at an expected false negative rate of 5%. As expected, these misclassification rates are higher than the false negative rate of 3.6% at a false positive rate of 2.6% found previously due in part to the absence of “% DNA methylation” and “8‐OHG” in the validation data, two of the most important variables for separating ASD and TD cohorts . CART and LR of a subset of metabolites produced results that were slightly worse than PCA with false positive rates of 38/154 and 32/154, respectively; both of these results are at an expected false negative rate of 5%.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…The FDA‐sub model had the best validation performance with a false positive rate of 19/154 at an expected false negative rate of 5%. As expected, these misclassification rates are higher than the false negative rate of 3.6% at a false positive rate of 2.6% found previously due in part to the absence of “% DNA methylation” and “8‐OHG” in the validation data, two of the most important variables for separating ASD and TD cohorts . CART and LR of a subset of metabolites produced results that were slightly worse than PCA with false positive rates of 38/154 and 32/154, respectively; both of these results are at an expected false negative rate of 5%.…”
Section: Discussionsupporting
confidence: 46%
“…The folate‐dependent one‐carbon metabolism (FOCM) and transsulfuration (TS) pathways comprise a promising source for a multivariate biomarker for ASD. These pathways incorporate both genetic and environmental factors linked to ASD liability . The authors have previously developed a multivariate biomarker, based upon Fisher Discriminant Analysis (FDA) for ASD that achieved a positive predictive value and negative predictive value of 97.6 and 96.1%, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The folate pathways are connected to several other important pathways that are abnormal in ASD (Figure 2). Biomarkers in these pathways may also be useful in understanding ASD, detecting ASD early, diagnosing ASD, predicting treatment response and identifying ASD subtypes [62]. However, further research is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, metabolic markers of oxidative stress were previously detected in plasma from autistic subjects(Frye and James, 2014; Howsmon et al , 2017; James et al , 2004; Melnyk et al , 2012; Rose et al , 2012b). It has been demonstrated that micronutrient supplementation targeting redox metabolism exerts beneficial effects on some children with autism, implicating the presence of oxidative stress in autistic brains(Blossom et al , 2012; Frye et al , 2013; Hamlin et al , 2013; Hendren et al , 2016).…”
Section: Discussionmentioning
confidence: 99%